Sodium supplementing material and preparation method thereof, positive pole piece and sodium ion battery
By using sodium supplementary materials with composite catalysts with core-shell structures in sodium ion batteries, the problems of high oxidation and decomposition potential and serious metal ion shuttle effect in sodium ion batteries are solved, and the effect of improving energy density and cycling performance is achieved.
Patent Information
- Application Number
- CN202411829459.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
In existing sodium ion batteries, the oxidation and decomposition potential of sodium supplementary materials is high, resulting in a decrease in electrochemical performance. At the same time, the metal ion shuttle effect is serious, affecting the cycling performance.
A sodium supplement material is used, which includes an organic sodium supplement body and a conductive agent partially coated thereon and a composite catalyst. The composite catalyst has a core-shell structure, the core layer includes a metal oxide catalyst, and the shell layer includes an electrochemically stable material to reduce the oxidative decomposition potential and suppress the metal ion shuttle effect.
It effectively reduces the oxidation and decomposition potential of sodium supplementary materials, inhibits the metal ion shuttle effect, and improves the energy density and cycling performance of sodium ion batteries.
Smart Images

Figure CN119674078A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a sodium supplement material and a preparation method thereof, a positive electrode sheet, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries are expected to replace traditional lithium-ion batteries in the energy storage field due to their advantages such as low cost, abundant sodium resources and relatively high energy density.
[0003] Supplementing sodium to the positive electrode plate with an organic sodium supplement can reduce the adverse effects on the electrochemical performance of sodium-ion batteries caused by sodium loss, but conventional organic sodium supplements have a high oxidative decomposition potential. Although the oxidative decomposition potential of organic sodium supplements can be reduced by combining metal oxide catalysts with organic sodium supplements, the metal ion shuttle effect will occur at the same time, resulting in poor stability of the organic sodium supplement, affecting the cycle performance of sodium-ion batteries. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a sodium supplement material and a preparation method thereof, a positive electrode plate, and a sodium ion battery, so as to reduce the oxidative decomposition potential of the sodium supplement material while inhibiting the metal ion shuttle effect, thereby improving the energy density and cycle performance of the sodium ion battery.
[0005] In the first aspect, the present application provides a sodium-supplementing material, comprising an organic sodium-supplementing agent body and a conductive agent and a composite catalyst at least partially encapsulated in the organic sodium-supplementing agent body; the composite catalyst has a core-shell structure, the core layer of the core-shell structure comprises a metal oxide catalyst, and the shell layer of the core-shell structure comprises an electrochemically stable material, and the electrochemically stable material is a material that has electrochemical stability under charge and discharge test conditions of a first-cycle charging voltage of 4.1V to a first-cycle discharge voltage of 1.5V and a cycle charging voltage of 3.5V to a cycle discharge voltage of 1.5V.
[0006] In some embodiments of the present application, the thickness of the shell layer is 1 nm to 5 nm.
[0007] In some embodiments of the present application, the mass percentage of the organic sodium supplement agent body in the sodium supplement material is a, the mass percentage of the conductive agent in the sodium supplement material is b, and the mass percentage of the composite catalyst in the sodium supplement material is c, 30%≤a≤90%, 0<b≤70%, 0<c≤30%.
[0008] In some embodiments of the present application, 50%≤a≤80%, 5%≤b≤50%, and 5%≤c≤10%.
[0009] In some embodiments of the present application, the sodium supplement material satisfies at least one of the following characteristics:
[0010] a) the material of the organic sodium supplement comprises at least one of CH3COONa, Na2C4O4, Na2C2O4, C6H5Na3O7 and Na2C6O6;
[0011] b) the conductive agent comprises at least one of conductive carbon black, carbon nanotubes, Ketjen black, graphene and acetylene black;
[0012] c) the material of the metal oxide catalyst includes at least one of ruthenium dioxide, iron oxide, vanadium pentoxide, titanium dioxide, cobalt tetraoxide, α-manganese dioxide, δ-manganese dioxide and γ-manganese dioxide;
[0013] d) The electrochemically stable material includes at least one of aluminum oxide, β-manganese dioxide, nickel oxide, zinc oxide, tungsten carbide, titanium carbide, tantalum carbide and MXene materials.
[0014] In a second aspect, the present application provides a method for preparing the sodium supplement material as described in the first aspect, comprising the following steps:
[0015] Mixing an organic sodium supplementing agent, a conductive agent and a composite catalyst to obtain a sodium supplementing material precursor;
[0016] The sodium-supplementing material precursor is subjected to a first calcination treatment in an inert gas atmosphere, the calcination temperature is 300° C. to 500° C., the heat preservation time is 1 h to 8 h, and the sodium-supplementing material is obtained after cooling.
[0017] In some embodiments of the present application, during the calcination process, the organic sodium supplementer melts, so that the conductive agent and the composite catalyst are coated in the molten sodium supplementer; during the cooling process, the organic sodium supplementer solidifies, so that the conductive agent and / or the composite catalyst are at least partially coated in the body of the organic sodium supplementer.
[0018] In some embodiments of the present application, the preparation process of the composite catalyst includes:
[0019] adding a metal oxide catalyst into a solvent and mixing them to obtain a dispersion;
[0020] Adding an electrochemically stable precursor material to the dispersion to obtain a mixed solution, and performing a solvent removal treatment on the mixed solution to obtain a composite catalyst precursor;
[0021] The composite catalyst precursor is subjected to a second calcination treatment in an inert gas atmosphere, the calcination temperature is 400° C. to 600° C., and the heat preservation time is 4 h to 6 h, so as to obtain the composite catalyst with a core-shell structure.
[0022] In some embodiments of the present application, the electrochemically stable precursor material includes at least one of sulfate, chloride and fluoride salts corresponding to the metal ions in the electrochemically stable material.
[0023] In a third aspect, the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the sodium-supplementing material as in the first aspect, or the positive electrode active material layer comprises the sodium-supplementing material prepared by the preparation method as in the second aspect.
[0024] In a fourth aspect, the present application provides a sodium ion battery, the sodium ion battery comprising the positive electrode plate of the third aspect.
[0025] In a fifth aspect, the present application provides an energy storage device, comprising a housing and at least one sodium-ion battery according to the fourth aspect, wherein the sodium-ion battery is housed in the housing.
[0026] In a sixth aspect, the present application provides an electrical equipment, comprising the energy storage device of the fifth aspect, and the energy storage device supplies power to the electrical equipment.
[0027] Compared with the prior art, this application has at least the following beneficial effects:
[0028] The present application provides a sodium supplement material and a preparation method thereof, a positive electrode plate, and a sodium ion battery, wherein the sodium supplement material comprises an organic sodium supplement agent body and a conductive agent and a composite catalyst at least partially coated in the organic sodium supplement agent body; the composite catalyst has a core-shell structure, the core layer of the core-shell structure comprises a metal oxide catalyst, and the shell layer of the core-shell structure comprises an electrochemically stable material, and the electrochemically stable material is a material having electrochemical stability under charge and discharge test conditions of a first-cycle charging voltage of 4.1V to a first-cycle discharging voltage of 1.5V and a cycle charging voltage of 3.5V to a cycle discharging voltage of 1.5V. In the sodium supplement material of the present application, the conductive agent and / or the composite catalyst are at least partially coated in the organic sodium supplement body, forming a coating or semi-coating structure for the conductive agent and / or the composite catalyst, which is conducive to promoting electron transfer to the organic sodium supplement body, thereby reducing the oxidative decomposition potential of the sodium supplement material; at the same time, the composite catalyst has a core layer and a shell layer, the core layer is conducive to promoting multi-electron transfer, further reducing the oxidative decomposition potential of the sodium supplement material, and the shell layer forms a protective layer for the metal oxide catalyst, which can reduce the direct contact between the metal oxide catalyst and the electrolyte, and is conducive to improving the structural stability of the metal oxide catalyst in the core layer, reducing the metal ion shuttle effect of the metal oxide catalyst in the sodium supplement material, maintaining the stability of the SEI (Solid Electrolyte Interphase, solid electrolyte interface) film, reducing the irreversible loss of sodium, and improving the cycle performance of the sodium ion battery; and the conductive agent in the sodium supplement material can further improve the conductivity of the sodium supplement material. The sodium supplement material of the present application has the above-mentioned structural characteristics and material characteristics, and can suppress the metal ion shuttle effect while reducing the oxidative decomposition potential of the sodium supplement material, thereby improving the energy density and cycle performance of the sodium ion battery. When the sodium ion battery is used in an energy storage device, the capacity and service life of the energy storage device can be improved, thereby reducing the operating cost of the energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 This is a schematic diagram of the cross-sectional structure of a sodium supplement material according to an embodiment of the present application;
[0031] Figure 2 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;
[0032] Figure 3 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application.
[0033] Explanation of the reference numerals: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-organic sodium supplement body, 20-conductive agent, 30-composite catalyst, 31-core layer, 32-shell layer, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0036] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0037] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0038] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0039] In the related art, although the oxidation decomposition potential of the sodium supplement material can be reduced by introducing a metal oxide catalyst into the sodium supplement material, when the metal oxide catalyst is introduced, the metal oxide catalyst is prone to phase change and structural change under high pressure, and the generated metal ions shuttle to the negative electrode, that is, the metal ions produce a shuttle effect, which will induce the decomposition of the electrolyte and the change of the SEI membrane structure, resulting in the poor cycle stability of the sodium ion battery. How to suppress the shuttle effect while reducing the oxidation decomposition potential of the sodium supplement material to improve the energy density and cycle performance of the sodium ion battery has become a technical problem that needs to be solved urgently.
[0040] In view of this, the present application provides a sodium supplement material, referring to Figure 1 The sodium supplement material includes an organic sodium supplement body 10 and a conductive agent 20 and a composite catalyst 30 at least partially coated in the organic sodium supplement body 10. The conductive agent and the composite catalyst can both be granular; the composite catalyst 30 has a core-shell structure, the core layer 31 of the core-shell structure includes a metal oxide catalyst, and the shell layer 32 of the core-shell structure includes an electrochemically stable material. The electrochemically stable material is a material with electrochemical stability under the charge and discharge test conditions of the first cycle charging voltage of 4.1V to the first cycle discharge voltage of 1.5V and the cycle charging voltage of 3.5V to the cycle discharge voltage of 1.5V. In the sodium supplement material of the present application, the conductive agent and / or the composite catalyst are at least partially coated in the organic sodium supplement body, that is, the conductive agent and / or the composite catalyst can be completely coated by the organic sodium supplement body, or the conductive agent and / or the composite catalyst can be partially coated by the organic sodium supplement body, so that the organic sodium supplement body forms a coating or semi-coating structure for the conductive agent and / or the composite catalyst, which is beneficial to promote electron transfer to the organic sodium supplement body, thereby reducing the oxidative decomposition potential of the sodium supplement material; at the same time, the composite catalyst has a core layer and a shell layer, the core layer is beneficial to promote multi-electron transfer, further reducing the oxidative decomposition potential of the sodium supplement material, and the shell layer contains an electrochemically stable material to form a protective layer for the metal oxide catalyst, which can reduce the direct contact between the metal oxide catalyst and the electrolyte, and is beneficial to improve the structural stability of the metal oxide catalyst in the core layer, reduce the metal ion shuttle effect of the metal oxide catalyst in the sodium supplement material, maintain the stability of the SEI film, reduce the irreversible loss of sodium, and improve the cycle performance of the sodium ion battery; and the conductive agent in the sodium supplement material can further improve the conductivity of the sodium supplement material. The sodium supplement material of the present application has the above-mentioned structural characteristics and material characteristics, and can suppress the metal ion shuttle effect while reducing the oxidative decomposition potential of the sodium supplement material, thereby improving the energy density and cycle performance of the sodium ion battery. When the sodium ion battery is used in an energy storage device, it can improve the capacity and service life of the energy storage device, thereby reducing the operating cost of the energy storage device.
[0041] In the present application, the oxidation decomposition potential refers to the potential corresponding to the oxidation decomposition reaction of the sodium supplement material during the charging process.
[0042] The present application can perform charge and discharge tests on sodium ion batteries containing the above-mentioned electrochemically stable materials. Exemplarily, the charge and discharge test process is as follows: First, the sodium ion battery is charged to 4.1V at a constant current of 0.1 times (C), and then discharged to 1.5V at 0.1C. Subsequently, a cycle test is performed, that is, charging to 3.5V at a constant current of 1C, and then discharging to 1.5V at 1C, which is a charge and discharge cycle. After 300 charge and discharge cycles, the capacity retention rate of the sodium ion battery is calculated. If the capacity retention rate is not less than 90%, it is considered that the electrochemically stable material has electrochemical stability.
[0043] In some embodiments of the present application, the thickness of the shell layer is 1 nm to 5 nm. For example, the thickness of the shell layer is 1 nm, 2 nm, 3 nm, 4 nm or 5 nm. When the thickness of the shell layer is too small (for example, less than 1 nm), the electrolyte is still easy to penetrate the shell layer and contact the metal oxide catalyst, and metal ions are easily dissolved under high voltage, which increases the metal ion shuttling effect of the metal oxide catalyst; when the thickness of the shell layer is too large (for example, greater than 5 nm), the electron transfer resistance between the metal oxide catalyst and the organic sodium supplement agent increases, resulting in a decrease in the catalytic performance of the catalyst for the sodium supplement agent, which is not conducive to the reduction of the oxidation decomposition potential of the sodium supplement material. By regulating the thickness of the shell layer within the above range, it is possible to reduce the metal ion shuttling effect of the metal oxide catalyst in the sodium supplement material while reducing the oxidation decomposition potential of the sodium supplement material, which is beneficial to the improvement of the energy density and cycle performance of the sodium ion battery.
[0044] In some embodiments of the present application, the mass percentage of the organic sodium supplementing agent in the sodium supplementing material is a, the mass percentage of the conductive agent in the sodium supplementing material is b, and the mass percentage of the composite catalyst in the sodium supplementing material is c, 30%≤a≤90%, 0<b≤70%, 0<c≤30%; in other embodiments of the present application, 50%≤a≤80%, 5%≤b≤50%, 5%≤c≤10%. For example, a is 30%, 40%, 50%, 60%, 70%, 80% or 90%; b is 1%, 10%, 15%, 20%, 30%, 40%, 50% or 70%; c is 5%, 6%, 7%, 8%, 9% or 10%. By regulating the contents of the organic sodium supplement agent, the conductive agent and the composite catalyst in the sodium supplement material within the above range, it is beneficial to obtain a sodium supplement material with low metal ion shuttling effect, low oxidation decomposition potential and excellent conductivity, which is beneficial to improving the energy density and cycle performance of sodium ion batteries.
[0045] In some embodiments of the present application, the material of the organic sodium supplement includes at least one of CH3COONa, Na2C4O4, Na2C2O4, C6H5Na3O7 and Na2C6O6. The above sodium supplement is an organic sodium supplement, which has the advantages of being environmentally friendly, widely available, safe and non-toxic.
[0046] In some embodiments of the present application, the conductive agent includes at least one of conductive carbon black, carbon nanotubes (CNT), Ketjen black (KB), graphene and acetylene black (ACET). The above conductive agent has the characteristics of good conductivity and large specific surface area, can improve the conductivity of the sodium supplement material, and is conducive to reducing the oxidation decomposition potential of the sodium supplement material.
[0047] In some embodiments of the present application, the material of the metal oxide catalyst includes at least one of ruthenium dioxide (RuO2), ferric oxide (Fe2O3), vanadium pentoxide (V2O5), titanium dioxide (TiO2), cobalt tetraoxide (Co3O4), α-manganese dioxide (α-MnO2), δ-manganese dioxide (δ-MnO2) and γ-manganese dioxide (γ-MnO2). The above metal oxide catalyst is conducive to reducing the oxidative decomposition potential of the sodium supplement material, thereby helping to improve the sodium supplement effect of the sodium supplement material.
[0048] In some embodiments of the present application, the electrochemically stable material includes at least one of aluminum oxide (Al2O3), β-manganese dioxide (β-MnO2), nickel oxide (Ni2O3), zinc oxide (ZnO), tungsten carbide (WC), titanium carbide (TiC), tantalum carbide (TaC) and MXene (two-dimensional structured transition metal carbon / nitride) materials. The above materials are conducive to maintaining the structural stability of the metal oxide catalyst during the charge and discharge process and reducing the metal ion shuttle effect of the metal oxide catalyst in the sodium supplement material.
[0049] In a second aspect, the present application provides a method for preparing the sodium supplement material as described in the first aspect, comprising the following steps:
[0050] Step A, mixing an organic sodium supplementing agent, a conductive agent and a composite catalyst to obtain a sodium supplementing material precursor;
[0051] Step B: performing a first calcination treatment on the sodium supplement material precursor under an inert gas atmosphere, the calcination temperature is 300° C. to 500° C., the insulation time is 1 h to 8 h, and the sodium supplement material is obtained after cooling.
[0052] In step A, raw materials such as an organic sodium supplementing agent, a conductive agent and a composite catalyst can be proportioned according to the content of components in the designed sodium supplementing material, and then mixed evenly to form a sodium supplementing material precursor.
[0053] In step B, the inert gas includes at least one of nitrogen and argon; the calcination temperature is preferably 4h to 5h; and the cooling process can be natural cooling. In addition, after cooling to obtain the sodium-supplementing material, the sodium-supplementing material can also be crushed by a crusher and then sieved to obtain the sodium-supplementing material in the desired particle size range, which is not particularly limited in this application.
[0054] In some embodiments of the present application, during the first calcination treatment, the organic sodium supplement agent melts, so that the conductive agent and the composite catalyst are coated in the molten sodium supplement agent; during the cooling process, the organic sodium supplement agent solidifies, so that the conductive agent and / or the composite catalyst are at least partially coated in the organic sodium supplement agent body. Through the above-mentioned calcination and cooling process of the present application, the conductive agent and / or the composite catalyst can be at least partially coated in the organic sodium supplement agent body, forming a coated or semi-coated structure for the conductive agent and / or the composite catalyst, thereby forming a sodium supplement material having the structure of the present application, and the prepared sodium supplement material has a lower oxidative decomposition potential.
[0055] In some embodiments of the present application, the preparation process of the composite catalyst includes:
[0056] Step i: adding a metal oxide catalyst into a solvent and mixing to obtain a dispersion;
[0057] Step II: adding the electrochemically stable precursor material to the dispersion to obtain a mixed solution, and performing a solvent removal treatment on the mixed solution to obtain a composite catalyst precursor;
[0058] Step III: performing a second calcination treatment on the composite catalyst precursor under an inert gas atmosphere, the calcination temperature is 400° C. to 600° C., and the insulation time is 4 h to 6 h, to obtain a composite catalyst with a core-shell structure.
[0059] In step i, the solvent is water, for example, distilled water or deionized water.
[0060] In step ii, the method for desolventizing is: vacuum drying the mixed solution at 60°C to 110°C to evaporate the solvent.
[0061] In step iii, through the second calcination treatment process of the present application, that is, regulating the calcination temperature and the insulation time within the above-mentioned range, the metal oxide catalyst in the composite catalyst precursor does not decompose, while the electrochemically stable precursor material decomposes to generate corresponding oxides or carbides, forming an electrochemically stable material, which is conducive to obtaining the composite catalyst of the present application.
[0062] In some embodiments of the present application, the electrochemically stable precursor material includes at least one of sulfate, chloride and fluoride salts corresponding to the metal ions in the electrochemically stable material. Exemplarily, when the electrochemically stable material is aluminum oxide, the corresponding electrochemically stable precursor material includes but is not limited to at least one of Al2(SO4)3, AlCl3, and AlF3.
[0063] The preparation method of the sodium-supplementing material provided in the present application has the advantages of simple preparation process and wide source of raw materials. The prepared sodium-supplementing material has excellent sodium-supplementing performance and low cost, thereby improving the energy density and cycle performance of the sodium-ion battery while reducing the production cost of the sodium-ion battery, thereby reducing the operating cost of the energy storage device applied to the sodium-ion battery.
[0064] The present application also provides a positive electrode plate, comprising a current collector and a positive electrode active material layer arranged on at least one surface of the current collector, the positive electrode active material layer comprising the sodium-supplementing material described in any of the above embodiments, or the positive electrode active material layer comprising the sodium-supplementing material prepared by the preparation method described in any of the above embodiments.
[0065] The positive electrode active material layer of the present application can be arranged on one surface or two surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode active material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode active material layer can be arranged in a partial area of one surface of the positive electrode current collector, or it can be arranged in the entire area of one surface of the positive electrode current collector. The present application has no special restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 13μm. The single-sided thickness of the positive electrode active material layer of the present application can be 150μm to 400μm.
[0066] In the present application, the positive electrode active material layer also includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, it may include at least one of sodium nickel manganate, sodium nickel iron manganate, sodium ferric sulfate, sodium vanadium phosphate, sodium copper iron manganate, sodium ferric pyrophosphate and sodium ferric pyrophosphate.
[0067] In the present application, the positive electrode active material layer may also include a positive electrode conductive agent. The present application has no particular restrictions on the positive electrode conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of conductive carbon black (SuperP), carbon nanotubes (CNT), Ketjen black (KB), graphene, graphene oxide and acetylene black. The mass percentage of the conductive agent in the positive electrode active material layer is 10% to 40%. In the present application, the positive electrode active material layer may also include a positive electrode binder. The present application has no particular restrictions on the positive electrode binder, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of fluorine-containing resin, polypropylene resin, fiber-type binder, rubber-type binder, polyimide-type binder and polyvinylidene fluoride (PVDF).
[0068] The present application also provides a sodium ion battery, comprising the positive electrode sheet described in any of the above embodiments.
[0069] The sodium ion battery of the present application also includes a negative electrode plate, a separator and an electrolyte, wherein the separator is located between the positive electrode plate and the negative electrode plate to play an isolation role.
[0070] The present application has no special restrictions on the negative electrode plate, as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer can be arranged on the surface of the negative electrode current collector, that is, the negative electrode active material layer can be arranged in a partial area of one surface of the negative electrode current collector, or it can be arranged in the entire area of one surface of the negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.
[0071] In the present application, the negative electrode active material layer may further include a negative electrode binder. The present application has no particular limitation on the negative electrode binder, as long as the purpose of the present application can be achieved, and for example, the negative electrode binder may include at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
[0072] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0073] The sodium ion battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then sodium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of sodium salt, as long as the purpose of the present application can be achieved. For example, the sodium salt may include at least one of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate and sodium p-toluenesulfonate. The present application has no particular restrictions on the concentration of sodium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of sodium salt is 1.0 mol / L to 2.0 mol / L.
[0074] The sodium ion battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.
[0075] The present application has no particular restrictions on the preparation method of the sodium ion battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the sodium ion battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a sodium ion battery.
[0076] The present application also provides an energy storage device, comprising a housing and at least one sodium ion battery in any of the above embodiments, wherein the sodium ion battery is contained in the housing. The energy storage device having the sodium ion battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more sodium ion batteries, and when the energy storage device contains multiple sodium ion batteries, the multiple sodium ion batteries may be connected in at least one of parallel and series.
[0077] The present application also provides an electrical device, including the energy storage device in any of the above-mentioned embodiments, which is conducive to improving the product competitiveness and performance of the electrical equipment. In an optional embodiment, the electrical equipment includes an electrical equipment body, and the energy storage device is used to supply power to the electrical equipment body. In an optional embodiment, the electrical equipment body includes a positive electrode of the device and a negative electrode of the device, and the positive electrode plate of the sodium ion battery in the energy storage device is used to electrically connect to the positive electrode of the device of the electrical equipment body, and the negative electrode plate of the sodium ion battery in the energy storage device is used to electrically connect to the negative electrode of the device of the electrical equipment body to supply power to the electrical equipment.
[0078] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0079] See also Figure 2 , Figure 2 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 2 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.
[0080] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0081] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 3 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.
[0082] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.
[0083] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0084] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.
[0085] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple sodium ion batteries of the present application in series / parallel, the battery pack may include multiple sodium ion batteries of the present application, and the battery system may be a charging and discharging system including the sodium ion battery or battery pack of the present application.
[0086] The actual application form of the energy storage device 1 provided in this application can be, but is not limited to, the listed products, and can also be other application forms. This application does not strictly limit the application form of the energy storage device 1. This application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 can be at least one of a cylindrical battery, a square battery, etc.
[0087] Example
[0088] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0089] Example 1
[0090] <Preparation of Sodium Supplementing Materials>
[0091] 9.5 g of the metal oxide catalyst titanium dioxide (TiO₂) was added to 50 mL of water, and after mixing, a dispersion was obtained; 0.5 g of Al₂(SO₄)₃ was dissolved in the obtained dispersion to obtain a mixed solution, and the mixed solution was ultrasonically dispersed and stirred, and after solvent removal treatment (vacuum drying at 80 °C for 12 h), a composite catalyst precursor was obtained; then the composite catalyst precursor was subjected to a second calcination treatment under an argon atmosphere, the calcination temperature was 500 °C, and the heat preservation time was 5 h, to obtain a composite catalyst; the composite catalyst obtained after calcination was subjected to a crushing treatment by a crusher, and then a sieving treatment was carried out;
[0092] 4 g of commercially available Na₂C₄O₄ powder, 0.5 g of the obtained composite catalyst material, and 0.5 g of conductive carbon black (Super P) were physically mixed, and a first calcination treatment was carried out under an argon atmosphere, the calcination temperature was 350 °C, the heat preservation time was 5 h, and the heating rate was 5 °C / min, to obtain a sodium supplement material; the sodium supplement material obtained after calcination was subjected to a crushing treatment by a crusher, and then a sieving treatment was carried out for later use.
[0093] <Preparation of Sodium-Supplemented Material Electrode>[
[0094] The prepared sodium supplement material, conductive agent Ketjenblack (KB), and binder PVDF were mixed according to a mass ratio of 60:30:10, solvent N-methylpyrrolidone (NMP) was added, and the mixture was stirred evenly to obtain a sodium supplement material slurry with a solid content of 60%. Then, the sodium supplement material slurry was evenly coated on an aluminum foil with a thickness of 10 μm, the single-sided coating thickness was 20 μm, and then vacuum drying was carried out at 110 °C for 12 h to obtain a sodium supplement material electrode. The obtained sodium supplement material electrode was cut into circular pieces with a diameter of 14 μm for later use.
[0095] <Preparation of NFPP Positive Electrode>[
[0096] The positive electrode active material Na₄Fe₃(PO₄)₂(P₂O₇) (i.e., NFPP), the prepared sodium supplement material, conductive agent Ketjenblack, and binder PVDF were mixed according to a mass ratio of 75:5:10:10, then NMP was added, and the mixture was stirred evenly to obtain a positive electrode slurry with a solid content of 60%. Then, the positive electrode slurry was evenly coated on an aluminum foil with a thickness of 10 μm, the single-sided coating thickness was 20 μm, and then vacuum drying was carried out at 110 °C for 12 h to obtain an NFPP positive electrode. The obtained NFPP positive electrode was cut into circular pieces with a diameter of 14 μm for later use.
[0097] <Preparation of Electrolyte>[
[0098] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1, and then sodium salt NaClO4 was added and dissolved in the above solvent, and then mixed evenly to obtain an electrolyte. The molar concentration of NaClO4 in the electrolyte was 1 mol / L.
[0099] <Preparation of Separator>
[0100] A glass fiber membrane with a thickness of 260 μm was selected as the diaphragm.
[0101] <Assembly of button cell battery>
[0102] <Assembly of the first button battery>
[0103] A circular sodium sheet with a diameter of 14 μm was used as the counter electrode. The circular sodium-supplementing material electrode sheet, diaphragm and circular sodium sheet prepared above were stacked in order, so that the diaphragm was placed between the circular sodium-supplementing material electrode sheet and the circular sodium sheet to play an isolating role. Then the prepared electrolyte was injected to assemble the first button battery.
[0104] <Assembly of the Second Button Battery>
[0105] A hard carbon negative electrode disc with a diameter of 14 μm was used as the counter electrode. The ratio of the battery negative electrode capacity to the positive electrode capacity (i.e., the N / P ratio) was 1.3. The NFPP positive electrode sheet, diaphragm and hard carbon negative electrode disc prepared above were stacked in order, so that the diaphragm was placed between the NFPP positive electrode sheet and the hard carbon negative electrode disc to act as an isolate. Then the prepared electrolyte was injected to assemble the second button battery.
[0106] Embodiment 2 to Embodiment 4
[0107] Except that in <Preparation of Sodium Supplementing Material>, the addition amount of the metal oxide catalyst and the electrochemically stable precursor material is adjusted according to Table 1, the rest is the same as Example 1.
[0108] Embodiment 5-embodiment 6
[0109] Except that the type of the metal oxide catalyst is adjusted according to Table 1 in <Preparation of Sodium Supplementing Material>, the rest is the same as Example 1.
[0110] Embodiment 7 to Embodiment 10
[0111] Except that the calcination temperature and the holding time of the second temperature are adjusted according to Table 1 in <Preparation of Sodium Supplementing Material>, the rest is the same as Example 1.
[0112] Example 11 to Example 12
[0113] Except that the amount of sodium supplement agent added was adjusted according to Table 2 in <Preparation of sodium supplement material>, the rest was the same as Example 2.
[0114] Embodiment 13
[0115] Except that the type of sodium supplement agent is adjusted according to Table 2 in <Preparation of sodium supplement material>, the rest is the same as Example 2.
[0116] Example 14 to Example 16
[0117] Except that the relevant parameters of the first calcination treatment are adjusted according to Table 3 in <Preparation of Sodium Supplementing Material>, the rest is the same as Example 2.
[0118] Comparative Example 1
[0119] Except that the composite catalyst is replaced by TiO2 catalyst in <Preparation of Sodium Supplementing Material>, the rest is the same as Example 1.
[0120] Comparative Example 2
[0121] No sodium supplement material is prepared, that is, no first button cell is prepared, and the NFPP positive electrode sheet does not contain sodium supplement material so that the prepared second button cell also does not contain sodium supplement material, and the rest is the same as Example 1.
[0122] Test methods and equipment:
[0123] Test on relative content of sodium supplement in sodium supplement material:
[0124] The sodium supplement material was quantitatively analyzed by inductively coupled plasma emission spectrometry (ICP): the sodium supplement material sample was tested by the main element method, and the element content of the tested sodium (Na) element was C0, then the content of the sodium supplement agent in the sodium supplement material sample was That is the relative content of sodium supplement.
[0125] Oxidative decomposition potential test:
[0126] The first button cell was subjected to the first cycle charge and discharge test using the LAND test system to obtain a differential capacity curve (dQ / dV curve). The oxidation peak of the dQ / dV curve corresponds to the oxidation decomposition reaction of the sodium supplement material, and the potential corresponding to the oxidation peak of the dQ / dV curve is the oxidation decomposition potential of the sodium supplement material.
[0127] Observation of the morphology of sodium-supplemented materials:
[0128] The cross section of the sodium supplementing material or the cross section of the positive electrode active material layer is subjected to ion beam profile grinding to obtain the cross section of the sodium supplementing material. The cross section area of the obtained sodium supplementing material is subjected to EDS (Energy Dispersive Spectroscopy) test with a magnification of 10K to 50K. The cross section of the sodium supplementing material shows a uniform distribution of the metal elements of the composite catalyst. At the same time, the surface of the sodium supplementing material is subjected to SEM (Scanning Electron Microscope) and EDS tests with a magnification of 10K to 50K. The surface of the sodium supplementing material also shows a uniform distribution of the metal elements of the composite catalyst, indicating that in the sodium supplementing material, the organic sodium supplementing agent body forms a coating or semi-coating structure with the conductive agent and / or the composite catalyst.
[0129] Composite catalyst shell thickness test:
[0130] The cross section of the composite catalyst was observed by HRTEM (High-Resolution Transmission Electron Microscopy) with a magnification of 20 million to 50 million times. The inside of the cross section was darker and the outside was brighter. The thickness of the brighter area was measured, which was the shell thickness of the composite catalyst.
[0131] First cycle charging capacity and first cycle discharging capacity test:
[0132] The test temperature is 25℃. Charge the button cell to 4.1V at a constant current of 0.1 times (C). This is the charging stage. Let it stand for 10 minutes, then discharge it to 1.5V at a constant current of 0.5C. Let it stand for 10 minutes. This is the discharging stage. Record the charging capacity of the first charging stage as the first cycle charging capacity in mAh / g. Record the discharge capacity of the first discharging stage as the first cycle discharge capacity in mAh / g.
[0133] Cycle performance test:
[0134] The test temperature is 25℃. Charge the button cell to 3.5V at 1C constant current, and discharge it to 1.5V at 1C after standing for 10 minutes. The capacity obtained in this step is the initial discharge capacity C i , perform a 1C charge / 1C discharge cycle test for n cycles, and record the discharge capacity of the nth cycle. Cycle capacity retention rate = (discharge capacity of the nth cycle / initial discharge capacity C i )×100%.
[0135] Table 1: Preparation parameters of composite catalysts
[0136]
[0137] Table 2: Preparation parameters of sodium supplement materials
[0138]
[0139] In Table 2, “ / ” indicates that there is no relevant preparation parameter.
[0140] Table 3: First calcination treatment parameters of Example 2, Example 14 to Example 16
[0141] Calcination temperature (℃) Insulation time (h) Example 2 350 5 Embodiment 14 300 5 Embodiment 15 400 5 Example 16 500 5
[0142] Table 4: Test data of the first button cell of each embodiment and comparative example
[0143]
[0144]
[0145] In Table 4, “ / ” indicates that there is no relevant test data.
[0146] Table 5: Test data of the second button cell of each embodiment and comparative example
[0147]
[0148]
[0149] Combining Table 4 and Table 5, it can be seen from Examples 1 to 16 and Comparative Examples 1 to 2 that the sodium supplement material of Comparative Example 1 simply uses TiO2 catalyst, and does not use the composite catalyst of the present application. Although its first cycle discharge capacity is slightly improved compared with Comparative Example 2, it is still low, and its capacity retention rate after 300 cycles is also low. This may be because the sodium supplement material of Comparative Example 1 does not have the structure of the present application, resulting in a metal ion shuttle effect in the metal oxide catalyst in the sodium supplement material. This shuttle effect will induce the decomposition of the electrolyte and the change of the SEI structure, resulting in the sodium ion battery. The cycle stability deteriorates and the capacity retention rate decreases; Comparative Example 2 does not have a sodium supplement material, so the first cycle charging capacity and the first cycle discharging capacity of its second button battery are both low, and its energy density is low; while the first button battery of the present application has a higher initial charging specific capacity and a lower oxidation decomposition potential, and the first cycle discharge capacity and the capacity retention rate after 300 cycles of the second button battery of the present application are significantly improved compared to Comparative Example 1, and the first charge specific capacity and the first cycle discharge capacity of the second button battery of the present application are significantly improved compared to Comparative Example 2, and the capacity retention rate after 300 cycles is also improved to a certain extent compared to Comparative Example 2. It can be seen that the sodium supplement material of the present application not only has a low oxidation decomposition potential, but also can inhibit the shuttling of metal ions to the negative electrode, so that the energy density and cycle performance of the sodium ion battery are improved at the same time.
[0150] In the process of preparing the composite catalyst, parameters such as the type and addition amount of the metal oxide catalyst in the composite catalyst, the type and addition amount of the electrochemically stable precursor material, the calcination temperature and the holding time of the second calcination treatment will usually also affect the performance of the sodium supplement material. It can be seen from Examples 1 to 10 that, on the basis of the sodium supplement material having the structure of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a sodium supplement material with a low shuttle effect and a low oxidation decomposition potential, so that the energy density and cycle performance of the sodium ion battery are improved at the same time.
[0151] In the process of preparing the sodium-supplementing material, the content of the sodium-supplementing agent, the content of the carbon material, the type of the sodium-supplementing agent, the calcination temperature and the holding time of the first calcination treatment will usually also affect the performance of the sodium-supplementing material. It can be seen from Examples 11 to 13 and Examples 14 to 16 that, on the basis of the sodium-supplementing material having the structure of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a sodium-supplementing material with a low shuttle effect and a low oxidative decomposition potential, so that the energy density and cycle performance of the sodium ion battery are improved at the same time.
[0152] The above is a detailed introduction to a sodium supplement material and its preparation method, a positive electrode sheet, and a sodium ion battery disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application; at the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A sodium supplement material, characterized in that: It comprises an organic sodium supplement body and a conductive agent and a composite catalyst at least partially coated in the organic sodium supplement body; The composite catalyst has a core-shell structure, the core layer of the core-shell structure includes a metal oxide catalyst, and the shell layer of the core-shell structure includes an electrochemically stable material. The electrochemically stable material is a material that is electrochemically stable under charge and discharge test conditions of a first-cycle charging voltage of 4.1V to a first-cycle discharging voltage of 1.5V and a cycle charging voltage of 3.5V to a cycle discharging voltage of 1.5V.
2. The sodium supplement material according to claim 1, characterized in that The thickness of the shell layer is 1 nm to 5 nm.
3. The sodium supplement material according to claim 1, characterized in that The mass percentage of the organic sodium supplementing agent body in the sodium supplementing material is a, the mass percentage of the conductive agent in the sodium supplementing material is b, and the mass percentage of the composite catalyst in the sodium supplementing material is c, 30%≤a≤90%, 0<b≤70%, 0<c≤30%.
4. The sodium supplement material according to claim 3, characterized in that 50%≤a≤80%, 5%≤b≤50%, 5%≤c≤10%.
5. The sodium supplement material according to claim 1, characterized in that The sodium supplement material satisfies at least one of the following characteristics: a) the material of the organic sodium supplement comprises at least one of CH3COONa, Na2C4O4, Na2C2O4, C6H5Na3O7 and Na2C6O6; b) the conductive agent comprises at least one of conductive carbon black, carbon nanotubes, Ketjen black, graphene and acetylene black; c) the material of the metal oxide catalyst includes at least one of ruthenium dioxide, iron oxide, vanadium pentoxide, titanium dioxide, cobalt tetraoxide, α-manganese dioxide, δ-manganese dioxide and γ-manganese dioxide; d) The electrochemically stable material includes at least one of aluminum oxide, β-manganese dioxide, nickel oxide, zinc oxide, tungsten carbide, titanium carbide, tantalum carbide and MXene materials.
6. A method for preparing the sodium supplement material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing an organic sodium supplementing agent, a conductive agent and a composite catalyst to obtain a sodium supplementing material precursor; The sodium-supplementing material precursor is subjected to a first calcination treatment in an inert gas atmosphere, the calcination temperature is 300° C. to 500° C., the heat preservation time is 1 h to 8 h, and the sodium-supplementing material is obtained after cooling.
7. The preparation method according to claim 6, characterized in that: During the calcination process, the organic sodium supplement agent melts, so that the conductive agent and the composite catalyst are coated in the molten sodium supplement agent; during the cooling process, the organic sodium supplement agent solidifies, so that the conductive agent and / or the composite catalyst are at least partially coated in the organic sodium supplement agent body.
8. The preparation method according to claim 6, characterized in that: The preparation process of the composite catalyst comprises: adding a metal oxide catalyst into a solvent and mixing them to obtain a dispersion; Adding an electrochemically stable precursor material to the dispersion to obtain a mixed solution, and performing a solvent removal treatment on the mixed solution to obtain a composite catalyst precursor; The composite catalyst precursor is subjected to a second calcination treatment in an inert gas atmosphere, the calcination temperature is 400° C. to 600° C., and the heat preservation time is 4 h to 6 h, so as to obtain the composite catalyst with a core-shell structure.
9. The preparation method according to claim 8, characterized in that: The electrochemically stable precursor material includes at least one of sulfate, chloride and fluoride salts corresponding to the metal ions in the electrochemically stable material.
10. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active material layer arranged on at least one surface of the current collector, wherein the positive electrode active material layer comprises the sodium supplement material as described in any one of claims 1 to 5, or the positive electrode active material layer comprises the sodium supplement material prepared by the preparation method as described in any one of claims 6 to 9.
11. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 10.
12. An energy storage device, characterized in that: It comprises a casing and at least one sodium ion battery according to claim 11, wherein the sodium ion battery is accommodated in the casing.
13. An electrical equipment, characterized in that: It includes the energy storage device as described in claim 12, and the energy storage device supplies power to the electrical equipment.
Citation Information
Cited By
Sodium replenishment material and preparation method therefor, positive electrode sheet and sodium ion battery
WO2026012221A1
Sodium supplementing material and preparation method therefor, positive electrode sheet, and sodium-ion battery
WO2026124142A1